REQUIREMENTS FOR THE PREPARATION OF DESIGN DOCUMENTATION BASED ON BUILDING INFORMATION MODELING (BIM) TECHNOLOGY - Zafar Matniyazov; Ilkhom Giyosov; Zilola Rakhmatillaeva; Nizomiddin Buronov; Anzirat Nigmadjanova (Scholar Express Journal, 2024)
The article examines the requirements for preparing design documentation using Building Information Modeling (BIM) technology in Uzbekistan's construction industry. BIM optimizes design processes, automates the creation of drawings and documentation, and enhances coordination among project participants. Special attention is paid to the methods of implementing BIM, including the development of 3D models, adherence to standards, classification systems, and building parameter analysis. The main results of BIM implementation are presented, and the existing challenges and future prospects of this technology are discussed. A comprehensive analysis demonstrated that the successful adoption of BIM can significantly improve construction project management, drive industry digitalization, and increase its competitiveness at the international level
Keywords: Building Information Modeling; design documentation; 3D modeling; standards